Executive compensation and company performance: solutions found by recent corporate governance codes, the case of Portugal and wider issues - Morais, Filipe (Conferência - Investigação e Intervenção em Recursos Humanos, 2014)
Executive pay has been rising silently in past decades across the globe, with more expression in the US, but increasingly in the UK and Europe (Pryce et al, 2010; IPS, 2010; ILO, 2008; EPI, 2007;). The relation between executive pay and corporate performance has never been as questionable as it is today. The sub-prime crisis and the financial and economic collapse that follow brought this relation to enormous scrutiny by the media, academics and notably by regulatory bodies. Empirical studies (Supanvanij, 2008; Baum, Sarver and Strickland, 2004) and reports of official bodies (EU Commission, 2011; FCIR, 2011; Hutton, 2011) and broader consultation like the one conducted by BIS (2011), all have shown and confirmed that this relation that justifies executive compensation levels is flawed. This suggests that the underpinning theories, notably the agency theory, socio-economic (Fulmer, 2009; Kakabadse et al, 2004) and the stakeholder theory (Pryce et al, 2010) need to be re-examined. In the Portuguese case there are not any studies that allow for comparing with international trends. However, Portuguese media (Expresso, 2011) has published a number of articles criticizing the enormous amounts of money paid to executives (particularly in public companies or companies where government holds a golden share) in the middle of a recession and in a period where Portugal was seen as the next country to need bail-out cash to survive. Interestingly this trend seems to be seen right across the developed countries regardless of corporate governance traditions being shareholder or stakeholder oriented. In response to the enormous public scrutiny and signs of shareholder activism, regulatory bodies right across the developed world issued new codes of corporate governance (AFG, 2011; SEV, 2011; EU Commission; 2011; Coffee, 2010; FCR, 2010; CMVM, 2010) with a great emphasis on board evaluation, shareholder “say on pay” and in some cases, mandatory disclosure of ratio of CEO pay to median employee earnings. Interestingly, and despite similar trends and levels of compensation in Portugal, the CMVM (2010) regulations, has not included most of the measures neither pushed for more disclosure on pay multiples and government has done little to improve corporate governance and levels of executive pay in public companies. This paper aims at examining current trends in executive compensation and theories that seem to justify them and to analyse the different solutions found by regulatory bodies to enforce greater transparency and accountability of corporate boards. It finishes with some questions that need answer regarding the impact of current trends on company performance and wider society.